The role of the youth in the struggle against the apartheid regime in Thabamoopo District of the Lebowa Homeland, 1970-1994 : critical historical analysis - Phaladi, Ramadimetje Jeanette (My University, 2008)
The Black youth struggled against the apartheid regime as the title indicates because as Blacks the policy made them to suffer. They were oppressed in the country of their birth. Before the militant youth involvement in the liberation struggle in the 1970s there were a few Black youths who tried to force the government to relinquish its policy. They were unsuccessful. This was because they were opposed to the government as members of the various Black organisations. They were not united. SASO with its Black Consciousness philosophy brought unity amongst all the Black youth and put them on the vanguard of the struggle. These youth did not just mobilize and unite Blacks (organisation and non organisation members) through public criticism of the apartheid system. They also mounted physical attacks on enemy targets such as police stations etc. South Africa became ungovernable. This resistance compelled the government to release political prisoners and to relinquish power in 1994.
Thesis (M.A.) -- University of Limpopo, 2008.
Keywords: Liberation struggle; Black youth; Anti-Apartheid movements; Anti-Apartheid movements - South Afirca; Apartheid - South Africa; Youth - Political activity - South Africa.